2021
DOI: 10.3390/insects12110977
|View full text |Cite
|
Sign up to set email alerts
|

Glasshouse Evaluation of the Black Soldier Fly Waste Product HexaFrass™ as an Organic Fertilizer

Abstract: The mass farming of the black soldier fly (BSF; Hermetia illucens L.), to produce insect-based feed for livestock and fish, results in considerable amounts of insect frass, which contains substantial amounts of organic matter and bioavailable nutrients. Insect frass has shown good potential as a soil amendment and organic fertilizer. This study examined the effects of HexaFrass™ on the growth of common vegetables and herbs under glasshouse conditions. In an organically-rich potting mix, HexaFrass™ increased sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 26 publications
(50 reference statements)
1
6
0
Order By: Relevance
“…Nutritional and economic value of pakchoi and residual TRGs BSFL frass can provide sufficient nutrition for the growth of pakchoi similar to chicken manure (Figures 3A,C), but the nutrient content between them is not completely consistent. Similarly, BSFL frass applied to corn (Garttling et al, 2020), sweet potato (Romano et al, 2022), vegetables, and herbs (Borkent and Hodge, 2021) has the potential to be an effective organic fertilizer. Although the total nitrogen content in BSFL frass was lower than that in chicken manure (Figure 3A), this may be because nitrogen is a key factor in the transformation of BSFL crude protein during growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nutritional and economic value of pakchoi and residual TRGs BSFL frass can provide sufficient nutrition for the growth of pakchoi similar to chicken manure (Figures 3A,C), but the nutrient content between them is not completely consistent. Similarly, BSFL frass applied to corn (Garttling et al, 2020), sweet potato (Romano et al, 2022), vegetables, and herbs (Borkent and Hodge, 2021) has the potential to be an effective organic fertilizer. Although the total nitrogen content in BSFL frass was lower than that in chicken manure (Figure 3A), this may be because nitrogen is a key factor in the transformation of BSFL crude protein during growth.…”
Section: Discussionmentioning
confidence: 99%
“…However, an increase in the amount of fertilizer may cause negative effects. Borkent and Hodge (2021) used BSFL frass as a fertilizer to grow basil, lettuce, and parsley and found that excessive application of this fertilizer resulted in restricted root development.…”
Section: Discussionmentioning
confidence: 99%
“…However, the roots were healthy, as indicated by higher root biomass if 10% BSF was mixed into the soil-based substrate, compared to higher BSF application rates, i.e., the root elongation was suppressed by 30-50% at higher application rates (Table 2). In contrast, Borkent and Hodge (2021) reported that the application of BSF waste product increased the dry weight of the shoot and root of several herb and vegetable plants and had similar effects to other commonly-used organic fertilizers, such as chicken manure.…”
Section: Effects Of Bsf Residue On Red Amaranth Growth and Yieldmentioning
confidence: 97%
“…A number of researchers have conflated plant growth promoting activity associated with leftover waste byproducts recovered from Black Soldier fly (Hermetia illucens) larva (BSFL) processed feedstocks with BSFL frass even though it is generally well-known that much of the residual leftover byproduct, aside from frass, consists of leftover feedstock in varying stages of degradation, insect exuviate, and microorganisms [1][2][3][4][5][6][7][8]. Whereas there is no question that BSFL while feeding and growing off of feedstocks leave frass deposits in the feedstocks on which they feed, frass, separated free of contaminating residual leftover feedstocks processed by larvae has not heretofore been examined for its role in conferring to soil plant growth promoting activity upon its amendment into soil.…”
Section: Introductionmentioning
confidence: 99%